Investigations on the Effect of Inclination Angle on the Aerodynamic Performance of a Two-Stage Centrifugal Compressor of a Proton Exchange Membrane Fuel Cell System - Wenke Wang; Dengfeng Yang; Li Guo; Rui Wu; Xiangyi Zhou; Qian Zhang; Qingyi Kong; Leon Hu (Energies)
This study examines how leading-edge inclination angles affect a two-stage centrifugal compressor’s aerodynamic performance using numerical and experimental methods. Five impellers with varied inclination configurations were designed for both stages. The results show that negative inclination improves the pressure ratio and efficiency under near-choke conditions, with greater enhancements in the low-pressure stage. Positive inclination significantly boosts the pressure ratio and efficiency under near-stall conditions, particularly in the low-pressure stage. Negative inclinations optimize blade loading and choke flow capacity, while effectively reducing incidence angle deviations induced by interstage pipeline distortion and decreasing outlet pressure fluctuation amplitude in the high-pressure stage. Positive inclinations delay flow separation, suppress tip leakage vortices, and extend the stall margin.